Psychological well-being among college students: A study from Central India - Sharma, Arvind; Singh, Tej Pratap; Sharma, Richa; Dhakar , Jagmohan Singh; Bharti , Aditi (Asian Journal of Medical Sciences, 2022)
Background: Psychological well-being (PWB) is affected by age, physical health, personality, life experiences, socioeconomic status, and culture. Age is an important social determinant of health and age-based analysis is necessary to rectify one’s health and health care. Aims and Objectives: This study aims to assess the PWB of college students and to determine the correlation between age and PWB aspects. Materials and Methods: This cross-sectional study was conducted among 210 college students selected by simple random sampling. Ryff’s PWB scale, a 42-item version used for the assessment of PWB, and data were collected by self-administering questionnaires. Statistical Analysis: Internal consistency of the scale was estimated and descriptive statistics, independent samples t-test, and regression analysis were applied. Results: The mean age of the participants was 19.41±1.69 years and 61% were male. Cronbach’s alpha coefficient for internal consistency of Ryff’s PWB scale was 0.814 in this study. The mean of PWB was 205.42±11.04 and ≥20 years scored higher in all the parameters of PWB than <20 years, differences were (t=3.62, P=0.001) significant. Simple linear regression showed that age was a highly significant (P=0.002) predictor of PWB. Conclusion: The study illustrated that students of 20 years or more had better PWB in terms of all dimensions than <20 years-, and also suggested the need for future research, like, to deepen on the conceptual and relations between age and PWB, and to analyze the impact that social changes have toward age group on PWB.